Adonara Island NTT: Preservation Of Weaving Traditions and Sustainable Halal Tourism Destinations - Windu Baskoro (Universitas Ahmad Dahlan, 2025)
Introduction to The Problem: Adonara Island, located in East Flores Regency, East Nusa Tenggara (NTT), possesses rich cultural potential through its traditional woven fabrics that reflect a strong local identity and cultural values. However, its potential as a cultural-based tourism destination remains underexplored. Purpose/Objective Study: This study aims to evaluate the potential of Adonara Island as a tourist destination based on the weaving industry by integrating aspects of the creative economy, cultural preservation, and halal tourism development. Design/Methodology/Approach: The research employed a qualitative descriptive approach, focusing on actual field conditions. Primary data was collected through interviews with local stakeholders, while secondary data was obtained from literature, government reports, and community documentation. Data analysis was conducted using SWOT analysis supported by IFAS and EFAS matrices. Findings: The results indicate that Adonara Island holds significant potential as a leading destination for cultural tourism. The SWOT analysis places Adonara Island in the first quadrant (growth strategy), suggesting strong opportunities for development. The recommended strategy includes improving accessibility, developing Muslim-friendly facilities, and empowering local communities through training and incentives. Branding efforts are encapsulated under the name “Adonara Tenun Island,” targeting both domestic and international markets. Sustainable tourism principles are applied by integrating environmental and cultural conservation. Collaboration between government, private sector, and local communities is essential for building an inclusive tourism ecosystem.